Curative Effect of Cutaneous Ulcer Wound Repair Through a Novel Liquid Dressing After HpD‐PDT Treatment of Extramammary Paget's Disease—A Prospective, Semi‐Lesion Controlled, Pilot Study - Wang, Dixin; Zhao, Yan; Chang, Qihang; Wang, Peiru; Zhang, Guolong; Wang, Xiuli (Journal of cosmetic dermatology, 2025)
ABSTRACT Objective To evaluate the clinical efficacy and safety of a novel skin wound dressing in promoting the repair of the ulcer wound after the treatment of Extramammary Paget's Disease (EMPD) with Hematoporphyrin Derivative Photodynamic Therapy (HpD‐PDT). Method A total of 10 patients with EMPD previously treated with HpD‐PDT were recruited to conduct a self semi‐lesion controlled study on the treatment of conformal dressing to evaluate the efficacy and safety of the skin ulcer wound repair therapy after HpD‐PDT. The skin lesions treated with novel HVHA Shutai dressing were the study intervention group, and the skin lesions treated with standard of care were the control group. Parameters including skin lesion wound area and adverse events were collected and analyzed in both groups, and wound healing rates were calculated. Results The mean total healing time of 10 subjects was 14.80 ± 3.36 weeks on the study intervention side and 18.30 ± 4.16 weeks on the control side. The total healing time of the study intervention side was significantly less than that of the control side (p = 0.009). The average healing rate of the test side was 85.28% ± 17.15% at Week 12, and that of the control side was 70.48% ± 23.20% at Week 12. The average healing rate of the study intervention side was significantly higher than that of the control side at Week 12 (p = 0.004). All skin lesions were completely healed at the end of follow‐up. No adverse events such as dressing allergy, pain, or wound infection occurred in the subjects. Conclusion For skin wound care after HPD‐PDT treatment of EMPD, HVHA Shutai dressing can accelerate wound healing, promote skin tissue and cell regeneration, and significantly shorten the time for complete wound healing of skin lesions, with significant effectiveness and acceptable safety.